1976
DOI: 10.1016/s0022-5347(17)59207-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatorenal Artery Bypass in the Management of Renovascular Hypertension

Abstract: Infrequently, when the aorta cannot be used for a standard renal bypass operation because of a previous aortic operation, severe degenerative atherosclerosis or complete aortic thrombosis, a unilateral (hepatic) or bilateral (hepatic and splenic) visceral bypass should be contemplated. Patients with abdominal aortic aneurysms extending above the renal arteries might benefit from concomitant bilateral visceral bypass procedures followed by aortic replacement during the same operative session. The hepatic circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…The first report was by Libertino in 1976 and there followed sporadic publications over the next few years. 2,3 Nowadays, hepatorenal bypass can be a valuable option if debranching of the renal arteries is planned to improve sealing at a landing zone during an endovascular aortic repair (EVAR) or thoracic EVAR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first report was by Libertino in 1976 and there followed sporadic publications over the next few years. 2,3 Nowadays, hepatorenal bypass can be a valuable option if debranching of the renal arteries is planned to improve sealing at a landing zone during an endovascular aortic repair (EVAR) or thoracic EVAR.…”
Section: Discussionmentioning
confidence: 99%
“…Available treatments include conservative medical treatment, endovascular intervention, and open surgical repair. 1 -4 Endovascular therapy for atherosclerotic RAS has recently fallen out of favor after a number of studies showed no long-term benefit, although it may be necessary in selected cases. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the right kidney, a hepatorenal bypass is a useful surgical procedure in achieving renal revascularization. This approach was originally described by Libertino et al [3] in 1976 and its efficiency was later confirmed in a report by Chibaro et al [4].…”
mentioning
confidence: 81%
“…Our own group (May et al 1976) has found little benefit from intraoperative biopsy in predicting either control of blood pressure or improvement in renal function -a view shared by Lawrie et al (1980a), who placed most value on the kidney size and mass, rather than the histological features. On the other hand, Libertino et al (1980) and Ekestrom et al (1979) both found that knowledge of the renal histolo,gy was useful in deciding whether renal artery reconstruction was worthwhile. At present there is insufficient evidence on which to base a firm conclusion regarding the role of examining renal pathology in this situation.…”
Section: Controversies In Managementmentioning
confidence: 99%